William Styron papers - Styron, William, 1925-2006.; Styron, William, 1925-2006.; Styron, William, 1925-2006.; Styron, William, 1925-2006.; Styron, William, 1925-2006.
Chiefly holograph drafts and corrected galleys of books and articles by Styron including his novels titled Lie Down in Darkness (1951), The Long March (1955), Set This House on Fire (1960), and The Confessions of Nat Turner (1967). Also includes correspondence, speeches, reviews, research material, clippings, and photographs pertaining to his life and literary works.
Microfilm edition of containers 1-4 (Lie Down in Darkness) available
Microfilm edition of containers 9-12 (Confessions of Nat Turner) available
Microfilm produced from originals in the Manuscript Division.
Author and novelist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: American fiction; American literature; Fiction; Literature; Authors; Novelists